Autoradiography on deparaffinized tissue sections – A feasibility study with 68Ga-labeled PET-tracers. (November 2022) - Klebermass, Eva-Maria; Dengler, Anna; Weissenböck, Victoria; Ricken, Gerda; Wadsak, Wolfgang; Viernstein, Helmut; Hacker, Marcus; Mitterhauser, Markus; Philippe, Cecile
Abstract: Tissue available for retrospective research questions is often already paraffin-embedded for better preservation. However, in vitro autoradiography (AURA) is normally performed on cryopreserved tissue sections. We hypothesized a) that it would also be feasible with deparaffinized tissue sections, enabling the use of human paraffin-embedded tissue for in vitro AURA and b) that the results would be comparable to those obtained with corresponding cryosections. For that purpose, the clinically relevant oncological targets CXCR4, SSTR and PSMA were evaluated. In vitro AURA on deparaffinized tissue sections was feasible, but only with the two receptor ligands [ 68 Ga]Ga-PentixaFor and [ 68 Ga]Ga-DOTANOC. [ 68 Ga]Ga-PSMA-11 did not show any binding on deparaffinized tissue sections, suggesting that native tissue is required for an interaction between this inhibitor and the enzyme. Graphical abstract: Image 1 Highlights: In vitro AURA with deparaffinized tissue sections was extended to oncotargets relevant for theranostic imaging. In vitro AURA with deparaffinized tissue was successful for [ 68 Ga]Ga-PentixaFor and [ 68 Ga]Ga-DOTANOC. In vitro AURA with deparaffinized tissue sections was not feasible for the enzyme-binding tracer [ 68 Ga]Ga-PSMA.